Jan Shikshan Sansthan - Ministry of Skill Development and Entrepreneurship, Government of India scheme for non/neo literates – A case study - Yugant Patra (Adult Education Research Conference, 2023)
The Jan Shikshan Sansthan (JSS) (translated into English as People Education Institute) is an initiative of the Ministry of Skill Development and Entrepreneurship, Government of India to improve occupational skills and technical knowledge of non/neo literates and persons having a rudimentary level of education but not completing high school in rural and semi-urban areas. The initiative aims to increase efficiency, increase productive ability, and enhance livelihood opportunities for such individuals specially targeted towards underprivileged sections of society. With the transformation in the open economy and social setup of India over the years, this initiative has become important in the economic development of the population by imparting essential skills training, thereby enabling local vocational trades to grow, and creating new opportunities for the local communities. This case study will provide an overview of the JSS structure, setup of centers and institutions, popular courses, and success stories of the scheme. It will also provide insights into the scheme’s promotion of self-employment and facilitation towards better financial inclusion. It will also highlight the importance of polyvalent educational institutions like JSS in the march towards the digital economy of India.
Keywords: adult education; vocational training; digital economy; rural adult education